Certain issues in teacher advanced life lessons and the practice of building communism - Rajackas, V. (Psichologija, 1963)
One of the most pressing issues teaching the humanities at this time is their relationship with life and building up communism.The article primarily clarifies what is understood as humanities' relationship with life as well as questions the educational role of these disciplines. Underlines that it is important to equip our students with the necessary knowledge to be a member of society and make available the necessary life skills and abilities on the basis of material close at hand and understandable for students, using their experience.Furthermore, the article draws attention to the literary and historical specifics and emphasizes the need to fight against vulgarization and the establishment of artificial life relationships.The article gives specific examples of a variety of literary and historical teaching practices demonstrating the importance and the magnitude of the possibilities for teaching life lessons and the practice of building communism within the humanities. Students associate real life material easily and consciously embrace it. Such material makes it easier for students to turn knowledge into beliefs. A range of practical skills and abilities not only prepares students for life, but also helps them reinforce and consciously assimilate new knowledge.The article discusses the independent development of students' thought as well as their empowerment issues.Based on the outlined material, we can conclude that the humanitarian subjects' relationship with life is particularly important for the communist upbringing of the younger generation and preparation for creative work and active social activity, helps develop a positive attitude towards literature and history, such important things for a communist upbringing, and learning in general.
Keywords: Teaching history; teaching literature; teaching humanities